Filamentous Fungi Isolated from the EEZ along the West Coast of India - N., Prabhakaran; Gupta, Ranu (Fishery Technology, 2025)
Thirty nine isolates of filamentous fungi of the genera Alternaria, Cladosporium, Fusarium and Penicillium were isolated from 78 water samples of 15 stations during FORV Sagar Sampada cruise No. 24 (16-11-1986 to 04-12-1986). Cladosporium was dominant including the marine species C. herbarum. Most of the filamentous fungi isolated restricted themselves to the coastal areas and theislands indicating their terrigenous origin and adaptation to high salinity. Aeromycological studies of four laboratories and hydrographic winch area of the ship revealed the presence of Aspergillus, Cephalosporium, Curvularia, Drechslera, Fusarium and Penicillium. Fusarium was dominant followed by Aspergillus including A. flavus